Differences in the effects of two hexachlorobiphenyls on superoxide generation by polymorphonuclear leucocytes stimulated by N-formyl-methionyl-leucyl-phenylalanine and phorbol myristate acetate. - Iwata, M (1994)
The effects of hexachlorobiphenyls (HCBs) on superoxide (O2-) generation by guinea pig polymorphonuclear leucocytes were examined. 2,3,6,2',3',6'-HCB by itself had only a weak inductive effect on O2- generation. This compound, however, enhanced O2- generation stimulated by N-formyl-methionyl-leucyl-phenylalanine (FMLP) about twofold, but not the generation induced by phorbol myristate acetate (PMA). On the other hand, 3,4,5,3',4',5'-HCB suppressed O2- generation stimulated by both FMLP and PMA. The inhibitory potency of this compound was far greater with PMA (ID50, 5 microM) than with FMLP (ID50, 40 microM).